ANALISIS KEBUTUHAN PENANGANAN SIMPANG EMPAT GERUNG DI LOMBOK BARAT - Suteja, I Wayan (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011)
Traffic congestions, traffic violations, and queuing problems in Western Lombok Region were frequently occurred at the main intersection, in particular at four legged intersection of Gerung. This is caused by ineffective operation at the intersection e.g. the use of the area for parking and stopping of public transport (angdes and cidomo). Therefore, it is required to evaluate the the intersection performance and to propose the intersection management. Primary data collected includes geometric, environment condition and traffic data. Performance analysis was conducted for the existing condition (unsignalised intersection) and for the proposed new traffic signal. The analysis was based on IHCM 1997 method. The analysis for existing condition showed that the capacity of the intersection was 3,159 pcu/hour and the degree of saturation was 0.74. This indicated that traffic management is required to improve the intersection performance such as redesigning geometric and applying traffic signal
Keywords: intersection performance, capacity, delay, traffic signal.